Effect of design parameters of serpentine-shaped flat plate solar collector under Malaysia climate conditions - Mohd. Amirul Hilmi, Mohd Hanoin; Nor Amirah Safiah, Muhamad; Nadzirah, Mohd Mokhtar; Amir, Abdul Razak; Muhamad Sukri, Hadi (Semarak Ilmu Publishing, 2021)
Solar thermal energy plays a vital role in the industrial sector, especially for water heating applications. Further research to improve the efficiency of flat plate solar collectors by focusing on collector design modification is imperative. This research aimed to carry out an experimental investigation on comparative designs and fabrication approaches that deal with the analysis of flat plate solar collector thermal performance, thermal efficiency, the effect of various mass flow rates, and pressure drop analyses. In this paper, a different design modification of pipe collector with serpentine-shaped was established with different tube diameters (3/4-inch and 3/8-inch), and different pipe spacing (18.5 cm and 27.0 cm). Under the same heat radiation intensity and constant mass flow rate, a pipe collector with a tube diameter of 3/4-inch achieved 3.5% and 9.4% higher thermal performance and collector efficiency respectively compared to the tube diameter of 3/8-inch. Furthermore, the pipe collector with pipe spacing of 18.5 cm exhibited 4.3% and 12.6% higher thermal performance and collector efficiency respectively compared to pipe spacing of 27 cm. The relationship between collector efficiency and temperature difference was also investigated. Moreover, the effect of different mass flow rates was studied upon and it was found that a flow rate of 0.03 kg/s exhibited optimum thermal performance for the pipe collector. Additionally, a pressure drop was observed with the increase in flow rate, while decreases when the fluid temperature increases